ANALISIS PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTIONS (Studi Empiris pada Novotel Semarang) - Witasari, Lia (JURNAL BISNIS STRATEGI, 2009)
Turnover intentions in hospitality industry is a signal of the employee turnover in the industry. The company shall give a serious attention because a high turnover within a company can interrupt activities and productivities. Beside, turnover can also create instability and uncertainty of employee condition. According to the above, the researcher argues that it is necessary to have a further examination about the relationship between job satisfaction and organizational commitment, and turnover intentions in the hospitality industry.The deep theory analysis of variables affecting turnover intentions brings the researcher to develop a research model consisting of three variables which are job satisfaction, organizational commitment, and turnover intentions as well as three research hypotheses. Data of job satisfaction, organizational commitment and turnover intentions is obtained through interviews using questionnaires to 142 respondents who are employees of the Novotel Hotel. Then, data is analyzed using Structural Equation Modeling (SEM) Technique of Analysis.The result of the three research hypotheses test using SEM shows that job satisfaction has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on turnoverintentions, and job satisfaction statistically proven that it does not have any significant effect on turnover intentions.Based on that results, therefore the research questions are solved. That turnover intentions is affected by organizational commitment. Therefore, in order to push the turnover intentions in a low number, the management need to take efforts to improve the organizational commitment of the employees.